Experimental study of secondary flows above rough and flat interfaces in horizontal gas-liquid pipe flow. (April 2020) - Vollestad, P.; Angheluta, L.; Jensen, A.
Highlights: Planar and stereoscopic PIV applied to gas-phase of gas-liquid pipe flow. Transition from flat to rough interface inverts the direction of secondary flows. Direction of secondary flows well predicted by gradients in normal Reynolds stresses. Abstract: We perform an experimental analysis of stratified, co-current gas-liquid flow in a straight pipe, with the aim of investigating secondary flow structures in the gas-phase. Planar PIV (particle image velocimetry) of the pipe centerline as well as stereoscopic PIV of the pipe cross section is performed, considering cases where the interface is either rough (wavy) or flat. Results demonstrate that the interface morphology determines the direction of the secondary flow patterns. Over a flat interface, the secondary flow cells are directed up along the pipe centerline and down along the pipe walls. When the interface is rough (wavy), the direction of the secondary flow cells is reversed. Normalized by the peak axial velocity, the vertical velocity profile in the pipe centerline is seen to collapse to a common curve when the interface is flat, while results indicate that the normalized strength of the secondary flows increase with increasing surface roughness. An assessment of the Reynolds stresses in the cross section is performed, and the direction of the secondary flow cells are found to be well predicted by the dominant gradients of the radial and circumferential Reynolds stresses ( τrr and τθθ ) in the radial and circumferential direction respectively.